O coordenador pedagógico e seu papel articulador, formador e transformador na implementação da lei 10.639/03: possibilidades e desafios - Teixeira, Juliana Patricia de Lima (2019)
The research deals with the role of pedagogical coordinators in the implementation of Law 10.639 / 03 (modifying Law 9.394 of December 20, 1996, which establishes the guidelines and bases of national education), to include the obligatoriness of the subject "History and Afro-Brazilian Culture" in the official curriculum of the Education Network and provides other measures. It is a qualitative research carried out with six pedagogical coordinators of the São Paulo municipal network, in the form of questionnaires and interviews with one of the coordinators. Taking into account the fact that pedagogical coordinators are key subjects for the curricular organization, articulation of the Political Pedagogical Project and, mainly, for the continued formation of the teachers, it is expected that this work can highlight the paths discovered by these professionals to implement said law, as well as to identify the challenges they still face, fifteen years after the publication of the law, relating them to the history of black people and racism in Brazil. It is also sought, through the research, to identify the educational needs of Pedagogical Coordinators with regard to education for ethnic-racial relations, in other words, the theoretical-practical subsidies they need to support and mobilize discussions about racial issues, prejudice and discrimination in schools. The research relies primarily on Almeida and Placco (2009), Domingues (2014), Gomes (2010), Placco and Souza (2010), Regis (2016) and Santos (2009). The methodology of data analysis is based on the prose analysis assumptions (André, 1983). It can be stated, from the analysis of data produced and collected through the questionnaires and interviews, that the study discloses a great diversity of training and articulation actions developed by the pedagogical coordinators for the implementation of Law 10.639 / 03, such as the work developed in the PEA (Special Project for Action) and the constitution of collective spaces as moments of continuous formation and elaboration of pedagogical activities and projects with this theme. The research highlights that, for such purpose, pedagogical coordinators still face numerous challenges, like political discontinuity, the opposition of some teachers in discussing the theme and gaps in their own formation, which generate demands and training needs that must be considered by the Municipal Education Network